THE INFLUENCE OF SOCIAL POLICY AND INTERVENTION ON PUBLIC SATISFACTION IN THE SOCIAL SERVICES FOR WOMEN'S EMPOWERMENT AND CHILD PROTECTION OF CENTRAL PAPUA PROVINCE - Bakti, Adi Setia; Lambe, Kristian Hoegh Pride; Buku, Atus (Entrepreneurship Undergraduate Program at Amkop Business School, 2025)
This study analyzes the influence of social policies and interventions on community satisfaction at the Social Service for Women's Empowerment and Child Protection of Central Papua Province. Using a quantitative approach with multiple linear regression analysis techniques, data were obtained from 35 respondents through questionnaires, observations, and documentation. The results of the study indicate that the policies implemented do not have a significant effect on community satisfaction, which is caused by inconsistent implementation, lack of community participation, and minimal policy socialization. On the other hand, social interventions have a significant effect on community satisfaction, with the main factors being the relevance of the intervention to community needs, transparency of implementation, and the positive impacts felt. Simultaneously, social policies and interventions have a significant effect on community satisfaction, confirming that integrated management of these two aspects is essential to improve the effectiveness of social services. Therefore, the main recommendation is to strengthen the synergy of policies and social interventions by ensuring consistent implementation and increasing community involvement in the process of policy formulation and evaluation.